Variation of wavelet entropy in electroencephalogram signal during neurofeedback training. Issue 3 (24th September 2012) - Ghoshuni, Majid; Firoozabadi, Mohammad; Khalilzadeh, Mohammad Ali; Hashemi Golpayegani, Mohammad Reza
Abstract Neurofeedback training (NFT) has an important role in improvement of cognitive functions in both clinical and healthy individuals. In this study, variation of wavelet entropy during low beta NFT was investigated. To investigate the effect of low beta NFT on wavelet entropy, correlation between the change in low beta activity and the change in wavelet entropy was computed. The results revealed that there is a highly significant negative correlation between the change in low beta activity and wavelet entropy. The given outcome suggests that enhancing low beta activity through NFT associated with decrements in wavelet entropy. Furthermore, we discuss a new implementation of NFT, based on wavelet entropy for future research. © 2012 Wiley Periodicals, Inc. Complexity, 2012